Rethinking Patricia Asero Ochieng and Two Others v. The Attorney General and another - Omolo, Joseph (Journal of Intellectual Property and Information Technology Law, 2021)
In 2012, the High Court of Kenya at Nairobi declared Section 2 of the Anti-Counterfeit Act (ACA) unconstitutional because its enforcement would limit access to affordable and essential drugs and medicines and thereby undermine the right to life, human dignity and health as guaranteed under the Constitution of Kenya. This case review revisits this important judgement by Justice Mumbi Ngugi with the aim of analysing it for legal soundness. Further, this review discusses the likely impact of the judgement on the fight against counterfeit drugs and access to drugs in Kenya. On the other hand, there will be a comparison between Kenyan legal system and some foreign laws. The review argues that the judge applied the wrong legal principles in making her determination, arriving at a legally flawed conclusion, thereby nullifying the balance between the rights of intellectual property rights owners and users as established under the Industrial Property Act.
Keywords: Intellectual Property Rights; Generic Drugs; Parallel Imports; Proviso; Statutory Interpretation